2017
DOI: 10.1007/s00417-017-3756-0
|View full text |Cite
|
Sign up to set email alerts
|

Retinal VEGF levels correlate with ocular circulation measured by a laser speckle-micro system in an oxygen-induced retinopathy rat model

Abstract: The LSFG-Micro provided reproducible blood flow measurements in neonatal rats. Because of the vitreous blood vessels, measurement of only the retinal vessels was not possible. However, the MBR was higher in the OIR rats than in the control rats, and the MBR and %AVA were correlated, as were the MBR and retinal VEGF. The MBR may thus serve as an indicator of OIR severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Nevertheless, our results are comparable with a study done by Ermakova et al on type 1 DM patients, which shows a relationship between the tear VEGF level and the degree of various manifestations of DR [37]. Tear VEGF levels may also be more representative of the ocular level of VEGF, as they are in closer proximity and share a similar circulation [38]. However, tear VEGF levels may be exposed to atmospheric changes.…”
Section: Discussionsupporting
confidence: 88%
“…Nevertheless, our results are comparable with a study done by Ermakova et al on type 1 DM patients, which shows a relationship between the tear VEGF level and the degree of various manifestations of DR [37]. Tear VEGF levels may also be more representative of the ocular level of VEGF, as they are in closer proximity and share a similar circulation [38]. However, tear VEGF levels may be exposed to atmospheric changes.…”
Section: Discussionsupporting
confidence: 88%
“…However, a recent in-depth analysis of tear fluid using the Schirmer collection method revealed eight similar proteins previously found in the aqueous and vitreous humor, recognized exclusively for AMD 36 . We believe that the tear VEGF level reflects the ocular level of VEGF due to closer proximity and similar circulation 37 .…”
Section: Discussionmentioning
confidence: 91%
“…In addition, a meta-analysis suggested that polymorphisms in the angiotensin-converting enzyme (ACE) I/D may be a genetic biomarker of an increased risk of ROP ( 119 ). The mean blur rate (MBR) was higher in OIR rats than in the control group, and it was significantly correlated with avascular area/total retinal area (%AVA) and retinal VEGF, therefore, MBR could be used to assess the severity of OIR ( 120 ).…”
Section: Candidates Of Novel Potential Biomarkersmentioning
confidence: 99%